Քաղաքական խոսույթի առանձնահատկություններն ու սոցիալ- քաղաքական փաստարկումը - Ալիկ Հակոբյան (ՀՀ ԳԱԱ հրատ.)
Generally the researchers consider that the main subject of rhetoric is the political discourse. The sociologists, the linguists and other specialist think that due to social changes, globalization, technological development the language became a power, that’s why the speech having a political aim needs serious argumentation.
Keywords: Language and Literature